The Association Between Antipsychotics and Weight Gain and the Potential Role of Metformin Concomitant Use: A Retrospective Cohort Study - Hakami, Alqassem Y.; Felemban, Razaz; Ahmad, Rami Ghazi; Al-Samadani, Abdulrahman H.; Salamatullah, Hassan K.; Baljoon, Jamil M.; Alghamdi, Loay J.; Ramadani Sindi, Mostafa H.; Ahmed, Mohamed Eldigire (Frontiers in Psychiatry, 2022)
Background: Obesity and its complications are associated with several adverse effects that may cause a serious impact on health. Antipsychotics-induced weight gain (AIWG) is one of the major, yet often neglected side effects of first and second generations antipsychotics. Importantly, several researches have shown metformin to be effective in managing weight gain especially, with AIWG. This study investigated the effect of antipsychotics use on weight gain and the theory of metformin concomitant use on the prevention of AIWG. Methods: A retrospective cohort review of the medical records of patients from the psychiatry outpatient clinics in the National Guard Health Affairs, a tertiary hospital in King Abdulaziz Medical City in Jeddah from May 2016 to August 2021. The population of patients in psychiatric section was 4141. The sampling technique was a non-random consecutive sampling technique. Moreover, the included patients' records were divided to group 1 (patients on antipsychotics) and group 2 (patients using antipsychotics with Metformin). Results: Accordingto the study criteria, 395 patients' records were included. A total of 309 (78%) patients were using antipsychotics without metformin, which in this study were depicted as group 1. In addition, a total of 86 (22%) were using antipsychotics with metformin, which in this study were assigned as group 2. Out of Group 1 patients (n = 309), only 67 patients experienced weight loss (21.68%), 43 remained with no weight change (13.92%), and 199 experienced weight gain (64.4%). Out of Group 2 patients (n = 86), 35 patients experienced weight loss (40.7%), 18 patients remained with no weight change (20.93%), and 33 experienced weight gain (38.37%). In addition, group 1 had a mean weight change of 2.5 kg, whereas group 2 had a mean weight change of -0.04 kg. Conclusion: Statistical analysis revealed that patients on antipsychotics alone experienced weight gain, whereas the concomitant use of metformin showed reduction in the weight gain tendency. Thus, study outcomes indicate that concomitant use of metformin with antipsychotics might significantly reduce the AIWG.